Simulation of the impact of changes in the volume of production and export of products on the food security of the country: on the example of Ukraine - Shpak, Nestor; Matviyishyn, Yevhen; Dziurakh, Yurii; Gvozd, Maryana (Frontiers in Sustainable Food Systems, 2024)
Changes in the production of agricultural products in Ukraine are analyzed. Forecasting of the volume of exports of agricultural products from Ukraine until 2027 was carried out. The following factors were taken into account: projected changes in real GDP in those countries that are the main importers of these products; reduction of cultivated agricultural land caused by military actions; forecasted changes in the population of Ukraine during the forecast period. It was concluded that there are no threats to Ukraine's food security caused by changes in the production and export of agricultural products. The research was based on a forecasting method, which made it possible to take into account retrospective information and a number of internal and external factors affecting the processes of production and export of agricultural products. The sources of information were the data of the International Monetary Fund and the State Statistics Service of Ukraine. The hypotheses of the study were confirmed, and the results showed that the volume of production of agricultural products will be sufficient to support the population of the country, while maintaining the previous proportion of exports. At the same time, there is a potential for growth of the share of products that Ukraine can export. The forecast volumes of export of Ukrainian agricultural products obtained can serve as a guideline for regulating exports, taking into account the issue of food security in Ukraine.